Design of a low-cost Hand Gesture Controlled Automated Wheelchair - Mahmood, Mufrath; Rizwan, Md. Fahim; Sultana, Masuma; Habib, Md; Imam, Mohammad Hasan (Proceedings (IEEE Region 10 Symposium. Online), 2020)
Design and implementation of a low-cost hand gesture controlled automated wheelchair-using Arduino based microcontroller and Node MCU is presented in this paper. The main focus of this study is to control the wheelchair with the movement of the hand-wrist movement. Besides hand gestures, the wheelchair can also be controlled via Bluetooth technology. If any problem occurs during the hand gesture control, Bluetooth technology can help to control the wheelchair through assisting person. The design also has some additional features such as tracking the location of the wheelchair through GPS from anywhere of the world and emergency switching system to send messages to the assisting person through sensor-based network. Arduino Mega, Arduino Nano, NODE MCU, MPU 6050 Gyro sensor, Sonar Sensor, GPS Module, GSM Module, HC-05 Bluetooth Module, nRF Transceiver, and relay-based H-Bridge Motor Driver Circuits are used to design the wheelchair prototype. The designed wheelchair is comparatively simpler in a sense that if any person can able to move their wrist only, then he/she can operate the wheelchair. Some other types of wheelchair designs were proposed in literature which contains complex computing system along with processing biological signals such as EEG, EMG, and EOG etc. The good recording of these bio-signals is quite challenging for very elderly/movement disabled subjects and complex signal processing along with bulky computing systems are required to operate such types of wheelchair. In the proposed design, the hand gesture control system is designed such that it overcomes the necessity of extra sensors and complicated biological signal processing systems. The proposed technique will have a great impact on society because of its easier use and cheaper price compared to other automated wheelchair designs.